Penggunaan Serbuk Infus Bekatul Sebagai Bahan Baku Bekatul Dextrosa Agar Untuk Pertumbuhan Jamur - Mujahidah - Basarang; Mardiah Mardiah; Andi Fatmawati (Jurnal Ilmu Alam dan Lingkungan, 2020)
Rice bran is a waste of rice processing that can be used as a growth media of fungi because it contains high carbohydrates and high protein. Rice bran infusion is made in powder form using freeze-drying techniques to maintain the nutritional content of rice bran. This study aims to determine the level of carbohydrate and protein media made from bran infusion powder and determine the dose of bran infusion powder in the preparation of dextrose bran media. In this study using the Luff Schoorl method to measure the levels of carbohydrate media and the Kjeldhal method to measure the protein content of bran media. Candida albicans, Mallasezia furfur, Aspergillus fumigatus were inoculated in each medium. From this study, the highest levels of carbohydrate (9.11%) and protein (1.64%) were obtained in media using 200 g of rice bran infusion (iBDA200) and the lowest levels carbohydrate (0.44%) and protein (0.08%) wer obtained in media using 2 g of rice bran infusion powder (SBDA2). Growth of M. furfur, C. albicans and A. fumigatus the most fertile on iBDA200 media. This study shows that carbohydrate and protein content are higher in media made from bran infusion. 10 g of rice bran infusion powder (SDA10) best grows fungi but has no significant correlation with fungi growth.